2022
DOI: 10.3389/fcvm.2022.868521
|View full text |Cite
|
Sign up to set email alerts
|

L-Arginine Improves Cognitive Impairment in Hypertensive Frail Older Adults

Abstract: Cognitive impairment is a prevailing event in hypertensive patients and in frail older adults. Endothelial dysfunction has been shown to underlie both hypertension and cognitive dysfunction. Our hypothesis is that L-Arginine, which is known to ameliorate endothelial dysfunction, could counteract cognitive impairment in a high-risk population of hypertensive frail older adults. We designed a clinical trial to verify the effects of 4-weeks oral supplementation of L-Arginine on global cognitive function of hypert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 77 publications
0
7
0
Order By: Relevance
“…This dose has been chosen based on a previous study (Gambardella et al, 2021a) in which we had verified that this regimen was safe and effective in ameliorating oxidative metabolism of water polo players. The taste is fully buffered by the addition of anhydrous citric acid and sucrose (Fiorentino et al, 2021;Mone et al, 2022d). Hence, there were no differences in appearance, taste, or smell, between placebo and treatment.…”
Section: Methodsmentioning
confidence: 99%
“…This dose has been chosen based on a previous study (Gambardella et al, 2021a) in which we had verified that this regimen was safe and effective in ameliorating oxidative metabolism of water polo players. The taste is fully buffered by the addition of anhydrous citric acid and sucrose (Fiorentino et al, 2021;Mone et al, 2022d). Hence, there were no differences in appearance, taste, or smell, between placebo and treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Studies suggested that endothelial dysfunction was involved in both hypertension and cognitive impairment (10,11). Several medications, such as L-arginine, empagliflozin, choline, metformin, and others, have been found to improve endothelial function and may therefore be beneficial in enhancing cognitive function (12,(37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…A diagnosis of frailty status was made according to the Fried Criteria, as we previously reported ( 19 , 41 ):…”
Section: Methodsmentioning
confidence: 99%